2020
DOI: 10.1093/jmammal/gyaa131
|View full text |Cite
|
Sign up to set email alerts
|

Giant otter diet differs between habitats and from fisheries offtake in a large Neotropical floodplain

Abstract: Giant otters Pteronura brasiliensis are semiaquatic mammals that mainly eat fish, the abundance of which is affected by seasonal flooding and habitat structure. The piscivorous habits of giant otters lead to negative human perception and conflicts with fisheries. We compared giant otter feeding habits between seasons and habitats in the Southern Pantanal, Brazil, by analyzing feces collected between September 2008 and June 2011.We investigated whether habitat and season affected P. brasiliensis diet compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…was also well-represented in the giant otter's diet. The authors also found a variety of other fish genera in P. brasiliensis prey spectrum, in addition to reptiles, insects, mollusks, and crustaceans, the last two consumed in high frequencies (Leuchtenberger et al 2020). Thus, it is possible that Hg sources which resulted in moderate Hg levels in P. brasiliensis matrices (Fonseca et al 2005;Soresini et al 2021) may not correspond to the fish species herein analyzed, but to other prey items explored by the carnivoran.…”
Section: Elements Occurrence and Concentrations: As CD Hg And Pbmentioning
confidence: 95%
See 1 more Smart Citation
“…was also well-represented in the giant otter's diet. The authors also found a variety of other fish genera in P. brasiliensis prey spectrum, in addition to reptiles, insects, mollusks, and crustaceans, the last two consumed in high frequencies (Leuchtenberger et al 2020). Thus, it is possible that Hg sources which resulted in moderate Hg levels in P. brasiliensis matrices (Fonseca et al 2005;Soresini et al 2021) may not correspond to the fish species herein analyzed, but to other prey items explored by the carnivoran.…”
Section: Elements Occurrence and Concentrations: As CD Hg And Pbmentioning
confidence: 95%
“…Interestingly, a study conducted on P. brasiliensis diet in Miranda and Negro river basins (Leuchtenberger et al 2020) pointed out ‗Serrasalmus sp'.as the second most consumed fish, after only the trahira Hoplias sp.…”
Section: Elements Occurrence and Concentrations: As CD Hg And Pbmentioning
confidence: 99%
“…Other aspects involve the spatiotemporal dynamics of the environment, such as complex hydrological interactions and characteristics that influence processes of flooding and erosion (Lima et al, 2012;Duplaix et al, 2015). However, the species faces several threats to its habitat Groenendijk et al, 2015), such as pollution and the difficulty in establishing conservation units for the protection of giant otter populations in the Pantanal wetlands (Groenendijk & Hajek, 2002;Tomas et al, 2015;Leuchtenberger et al, 2020).…”
Section: Introductionmentioning
confidence: 99%